Pembelajaran Daring Menggunakan Simulasi PhET untuk Melatih Kemampuan Computational Thinking Peserta Didik - Satwika Trianti Ngandoh (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
This study aims to improve the skill of student’s SMP Negeri 14 Makassar of computational thinking on online learning using PhET simulation. This study applied classroom action research (PTK). Planning, action, observe and reflect in two cycles were employed. This study engaged grade IX students in the 2020/2021 academic year on Dynamic Electricity. The instrument that was used were observation and tests. The result showed that Computational Thinking using PhET simulation has achieved the target according to the indicators. The increasing from first cycle to second cycle was 53.84%. Therefore, it can be concluded that science studies using PhET simulation improved students' Computational Thinking.